2020
DOI: 10.1002/jobm.202000236
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization and purification of phytase from Lactobacillus plantarum CRL1964 isolated from pseudocereals

Abstract: Cereals and pseudocereals are a rich source of nutrients and trace elements, but their dietary bioavailability is low due to the presence of phytate (IP6), an antinutritional compound with the ability to chelate cations and proteins. Phytase is an enzyme that catalyzes the hydrolysis of IP6 and it is used as an additive improving the nutritional quality of grain‐based foods. The aim of this study was to select lactic acid bacteria (LAB) isolated from pseudocereals with phytase activity, characterize their prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Karagöz et al [11] reported the protein concentration of phytase purified from L. plantarum as 0.11 mg/mL. Sandez Penidez et al [26] reported the protein value of phytase enzyme partially purified from L. plantarum as 0.08 mg/mL. Demir et al [22] determined the protein amount of phytase purified from L. coryniformis as 0.12 mg/mL in their study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Karagöz et al [11] reported the protein concentration of phytase purified from L. plantarum as 0.11 mg/mL. Sandez Penidez et al [26] reported the protein value of phytase enzyme partially purified from L. plantarum as 0.08 mg/mL. Demir et al [22] determined the protein amount of phytase purified from L. coryniformis as 0.12 mg/mL in their study.…”
Section: Discussionmentioning
confidence: 96%
“…Dikbaş et al [8] determined the pH and temperature at which the phytase enzyme partially purified from L. brevis showed optimum activity as pH 3.0 and 60 °C, respectively. Sandez Penidez et al [26] found that L. plantarum CRL1964 (PhyLP) phytase exhibited optimum activity at pH 4.5 and 55°C. Based on the literature studies and the findings obtained, it is seen that the phytase enzyme purified from Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, phytase purified from L. kefiri (approx. 72 kDa) was found to have a higher molecular weight than Lactobacillus coryniformis (43.25 kDa) (Demir et al., 2018), L. plantarum CRL1964 (55 kDa) (Sandez Penidez et al., 2020), and L. brevis (49.9 kDa) (Dikbaş, Uçar, et al., 2023) and a similar molecular weight to L. plantarum (72 kDa) (Sumengen et al., 2013), L. brevis (73 kDa) (Sümengen et al., 2012), and L. paracasei (70 kDa) (Bhagat et al., 2019). Considering the literature studies and the results obtained, it is seen that the molecular weight of purified phytases can vary according to their source.…”
Section: Discussionmentioning
confidence: 99%
“…The main fermentation products generated by sourdough microbiota are mostly related to sensory attributes, such as volatile and phenolics compounds, and organics acids [44,[55][56][57][58]; however, some researchers have also found phytase, γ-aminobutyric acid (GABA), antioxidant and anti-inflammatory compounds, thus associating sourdough consumption with potential health benefits [41,56,[59][60][61][62].…”
Section: Fermentation Products Taxonomymentioning
confidence: 99%